Diseño e implementación de un sistema de costos por procesos para la planta de producción inladec industria láctea de Cotopaxi ubicado en el cantón Salcedo para el periodo enero-diciembre 2013 - Callatasig Simba, Nelly Patricia (2015)
The research carried out shows the design of a costs system by processes for the production factory INDALEC, it was based in the collecting of accounting and financial information through methods such as inspection, surveys and interviews, applied to customers and staff operates within the enterprise, they were also used for the previous valuation of the problem, and the definition of the critical part of the costs system. The result was that it isn´t applied a suitable costs system to value each of the processed products such as cheese….